The use of natural stone as a replacement at the Large church or St Mary-Magdalene church in Goes (Bulletin KNOB, 2009)
In this article the process of choice is examined leading to the application of specific types of natural stone as a replacement in restorations. For this purpose three consecutive restoration campaigns are analysed, which took place in the St Mary Magdalene church in Goes. The focus of attention is the question to what extent the architects involved took aspects of compatibility and sustainability into account in their choice. It appears that during the first two decades of the twentieth century the arguments of the choice were quite one-sidedly aimed at hardness, an assumed measure for sustainability. During the twenties of the twentieth century a variety of arguments led to a variety of types of stone, whereas during the latest restoration campaign in the nineties of the twentieth century the stress was once again on sustainability, with aesthetics playing a secondary role.During the latest restoration campaign the choice of a type of natural stone as a replacement no longer appears to be the only aspect of the restoration of the façade. Various cleaning techniques and the choice of mortar repairs instead of replacement by natural stone are playing an increasingly large role in the conservation of the monument.